2000
DOI: 10.1007/s10434-000-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Distant Soft Tissue Metastases: A Series of 30 New Patients and 91 Cases From the Literature

Abstract: In this musculoskeletal oncology referral-based clinical series, soft tissue metastases most commonly occur in patients with a painful soft tissue mass and no history of cancer. Lung is the most frequent primary source. Treatment should be individualized according to the underlying disease and its prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
153
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 43 publications
6
153
2
3
Order By: Relevance
“…Although the CT presentation did not conform to the typical skeletal muscle metastasis, which is rather rare, this suspicious diagnosis could not be ruled out solely relying on the imaging findings, particularly considering that NSCLC is prone to distant metastases (7). The differential diagnosis should include intramuscular metastasis and primary soft-tissue tumors, as each can arise from the psoas muscle and cause lumbar pain (13)(14)(15). Furthermore, the definition of the nature of the muscle abnormality would be of great value, as the correct diagnosis would affect the following clinical management and vary the prognosis of the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CT presentation did not conform to the typical skeletal muscle metastasis, which is rather rare, this suspicious diagnosis could not be ruled out solely relying on the imaging findings, particularly considering that NSCLC is prone to distant metastases (7). The differential diagnosis should include intramuscular metastasis and primary soft-tissue tumors, as each can arise from the psoas muscle and cause lumbar pain (13)(14)(15). Furthermore, the definition of the nature of the muscle abnormality would be of great value, as the correct diagnosis would affect the following clinical management and vary the prognosis of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent clinical manifestation of muscle metastasis is local pain, with or without a palpable mass (15). In individual cases, skeletal muscle metastasis from lung cancer has even presented as the initial clinical manifestation, so it may be easily misdiagnosed, particularly when the primary tumor is unknown (25).…”
Section: Discussionmentioning
confidence: 99%
“…The commonly reported primary malignancies that may metastasize to the skeletal muscle are lung cancer, renal cell carcinoma and gastrointestinal tumours and genital tumours, but rarely melanoma [13][14][15][16][17][18][19][20][21][22] . The best epidemiological evidence for skeletal muscle metastasis reported to date was from an 8-year retrospective review of Surov et al They reported an incidence of 1.2% out of 5,170 patients that presented with metastatic solid malignancies, and most of them (91.8%) already had widespread metastases when the distal skeletal muscle was found to be invaded, hence it's uncommon to see isolated intramuscular metastases without spreading to other distant organs as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The common clinical scenario in which skeletal muscle metastasis is detected is the presenting symptom of a painful mass (usually more than 5 cm in diameter) [13][14][15][16][17][18][19][20][21][22] . This may be an important clue to suggest metastasis rather than a primary sarcoma of soft tissue, which is more commonly seen but typically present as painless soft tissue masses [14,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Surov et al reported a series of 61 patients with skeletal muscle metastasis from a population of 5170 patients seen during a 7-year period [51]. Damron and Heiner described a series of 30 patients and identified an additional 91 cases from the literature [8]. Other, smaller series exist, including a series of 12 patients described by Tuoheti et al [53], and 11 patients described by Yoshimura et al [58].…”
Section: Discussionmentioning
confidence: 99%